Precipitation-induced mitigation of recrystallization in ultra-thin, cold-rolled AlScZrMn(Mg) sheets at brazing temperatures: The critical effect of alloy composition and thermal processing route. (March 2020) - Dong, Qingshan; Howells, Andrew; Gallerneault, Mary F.; Fallah, Vahid
Abstract: Using advanced electron microscopy techniques, statistical analysis and analytical investigation of precipitates/dispersoids evolution, we demonstrate the critical effect of alloy composition (Sc, Mn, and Mg content) and thermal processing route (heating rate and pre-aging) on the recrystallization behavior of AlScZrMn(Mg) alloys. Two major types of second phases, namely Al3 (Sc, Zr) precipitates and α-Al(Mn, Fe)Si dispersoids, were identified in the thermally-treated cold-rolled sheets (of 0.3 mm thickness). Both phases were observed to maintain coherency with the Al matrix at abnormally large sizes (>100 nm and >500 nm, respectively), as well as exhibiting unprecedented levels of thermal stability (i.e., high coarsening resistance). The recrystallization behavior and strength evolution were shown to be a strong function of the size and aerial number density evolution of the precipitates/dispersoids which, in turn, are controlled by the alloy composition and thermal history. Particularly, the recrystallization was effectively mitigated at a slow ramp to 590 °C (a typical brazing temperature for AlMn alloys) whereas a full recrystallization occurred during a faster ramp. Such behavior was explained by the competitive kinetics of Al3 (Sc, Zr) precipitation and recrystallization phenomenon at intermediate and high-temperature ranges upon heating to 590 °C. The introduction of a pre-aging treatment within the intermediate temperature range (i.e., 250–400 °C), prior to the fast ramp, was shown to prevent recrystallization due to the stabilization effect of a large aerial number density of finely-dispersed Al3 (Sc, Zr) precipitates. A higher Sc content in the alloy enhances such a stabilization effect. Mn additions not only enhance the mitigation of recrystallization (through a refinement of Al3 (Sc, Zr) precipitates) but also refines the evolution of α-Al(Mn, Fe)Si dispersoids resulting in a higher yield strength. The Mg addition, on the other hand, has no impact on the evolution of Al3 (Sc, Zr) precipitates nor on the recrystallization status, though it causes a refinement of α-Al(Mn, Fe)Si dispersoids and thus leads to a higher final yield strength. The extraordinary high-temperature stability of cold-rolled thin sheets, obtained by the alloy and process design in this study, can be effectively utilized for many light-weight applications of AA3xxx Al alloys. Graphical abstract: Image, graphical abstract